IMPLEMENTASI MODEL MINDMAPPING DALAM MENINGKATKAN KEMAMPUAN MENULIS SISWA PADA PEMBELAJARAN BAHASA ARAB DI SD IT NURUL IMAN PALEMBANG - Nanda Afuwannisa; Mukmin, Nurul Hidayah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of learning Kitab Takallam on maharah kitabah (writing skills) using the Mind Mapping model at SD IT Nurul Iman Palembang. Arabic language learning, particularly writing skills, is often perceived as difficult, monotonous, and less engaging for students. Therefore, the Mind Mappingmodel was applied as an innovative approach to enhance students’ creativity, involvement, and understanding of the material. This research employed a mixed-method design with a pre-test and post-test one group designwithout a control class. The subjects were 19 fifth-grade students at SD IT Nurul Iman Palembang. Data collection techniques included observation, interviews, documentation, and tests (pre-test and post-test). Data analysis was conducted qualitatively using Miles and Huberman’s model and quantitatively using normality tests, t-tests, and N-Gain Score. The results indicate a significant improvement in students’ writing skills after applying the Mind Mapping model, with higher post-test scores compared to pre-test scores. These findings demonstrate that the use of Mind Mapping in Kitab Takallam learning is effective in improving students’ maharah kitabah.